2022
DOI: 10.1186/s12877-022-03024-4
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes and implementation barriers and facilitators of comprehensive geriatric assessment in community settings: a systematic integrative review [PROSPERO registration no.: CRD42021229953]

Abstract: Background Comprehensive geriatric assessment (CGA) addresses the bio-psycho-social needs of older adults through multidimensional assessments and management. Synthesising evidence on quantitative health outcomes and implementation barriers and facilitators would inform practice and policy on CGA for community-dwelling older adults. Methods We systematically searched four medical and social sciences electronic databases for quantitative, qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 85 publications
0
32
0
Order By: Relevance
“…Although nephrologists and geriatricians recognised the relevance of geriatric assessment in older CKD patients [ 35 ], current evidence regarding its use in primary care (i.e. the presumable setting for community-dwelling older people with mild-to-moderate CKD) is mixed and barriers to implementation still need to be overcome and warrant further investigations [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although nephrologists and geriatricians recognised the relevance of geriatric assessment in older CKD patients [ 35 ], current evidence regarding its use in primary care (i.e. the presumable setting for community-dwelling older people with mild-to-moderate CKD) is mixed and barriers to implementation still need to be overcome and warrant further investigations [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review found low-certainty evidence that CGA in a community setting increases the likelihood of frail older people being able to remain at home and reduces the risk of unplanned hospital admission (12) but all the trials were geriatrican raher than GP-led . Another systematc review in community settings reported improvement in function, quality of life and mental health outcomes following CGA for older frail people (19). Most CGAs were conducted by geriatrician or geriatric nurses (12,19) (20).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Primary care (13) provides an ideal setting for routinely identifying high-risk patients (14), but there is no established model of frailty assessment and management (15) and limited evidence of effectiveness or cost effectiveness of community-based CGA (12,(15)(16)(17), even though an adapted CGA for use within general practice is recommended by the British Geriatrics Society (18). Barriers to implementation need further investigation (19). Research on community-based CGA shows wide variation in who conducts the assessment, including geriatric specialists (19,20), nurses, physiotherapists and social workers (19,21,22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Home-based CGA is an alternative to clinical CGA for the elderly in RACs for their care management to improve their quality of life [ 10 ]. There are many barriers and challenges to the implementation of CGAs in community settings [ 11 ], but in the context of early identification of health risks, it is difficult to identify the time for CGA to meet the needs of individuals as the health status could change rapidly and unexpectedly in the elderly [ 12 ]. Regardless of the challenges and limitations, CGA is a gold standard for the management of frailty [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%